Miocenske mitilide iz okolice Stolnika v Tunjiškem gričevju - Mikuž, Vasja (Geologija, 2009)
In the contribution Miocene molluscs from Tunjice hills are dealt with. At Stolnik were found stony casts of mytilid bivalves that are very rare in Slovenia. Other finds belong to bivalve families Crassatellidae, Cardiidae, and Veneridae. Frequent are in addition gastropods of family Turritellidae.
Keywords: fosili; mehkužci; miocen; polži; Slovenia; Slovenija; školjke; Tunjiško gričevje